2009
DOI: 10.5104/jiepeng.2.79
|View full text |Cite
|
Sign up to set email alerts
|

Pb-Free High Temperature Solder Joints for Power Semiconductor Devices

Abstract: Three types of inexpensive Pb-free solder joints, namely Zn-based and Bi-based solders, and a CuSn alloy were studied for application to the high-temperature operation of wide band-gap power semiconductor devices using GaN or SiC. ZnAl solder sheets, whose melting point is 380°C were prepared, and then surface oxides were removed by RF plasma etching. Subsequently, Cu thin films were deposited by the DC sputtering method on the solder sheet. After that, joint samples were fabricated using a conventional electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 2 publications
0
9
1
Order By: Relevance
“…For the former problem, Yamada and his coworkers indicated that the use of a Zn-Al solder sheet the surface of which was covered with thin film Cu could significantly improve wettability [5]. However, we could not duplicate their results with our experimental setup in spite of forming and using similar sheets.…”
Section: Resultscontrasting
confidence: 53%
“…For the former problem, Yamada and his coworkers indicated that the use of a Zn-Al solder sheet the surface of which was covered with thin film Cu could significantly improve wettability [5]. However, we could not duplicate their results with our experimental setup in spite of forming and using similar sheets.…”
Section: Resultscontrasting
confidence: 53%
“…Power semiconductor modules (Fig. 1) [1] that consist of many power semiconductor devices are used for these inverters and converters. Power semiconductor devices based on wide band gap materials such as SiC and GaN are promising for next-generation, high-temperature-operation devices [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Pb-5Sn) has been currently used for high temperature, there is a mandatory requirement to remove Pb from electronic components because of its toxicity [2,3]. Therefore, there have been several researches about alternative materials and processes without Pb, however there are still challenges to release thermal accumulation efficiently and endure high operation temperature [4][5][6].…”
Section: Introductionmentioning
confidence: 99%